Rancang Bangun Sistem Informasi Pengecekan Informasi Palsu (Hoax) Menggunakan Teknologi Single Page Application (SPA) dengan Metode Extreme Programming - Maulana, Mohammad Arfan; Cahyono, Yono (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2022)
Technology is often used by the public to share and find information on the internet through social media, websites, and others. The internet allows people to access information regardless of time and place, wherever and whenever, but one of the negative impacts that often occurs with the presence of the internet is the spread of false information (hoax). Sometimes it is very difficult to distinguish whether the information is true or false (hoax). The impact of the spread of false information is unrest and division in society. This study aims to design and create a website based system that can be used to check whether the information spread is true or false (hoax) by using Single Page Application (SPA) technology with extreme programming as its development method. This research produces a system that can make it easier for people to distinguish between false and true information.